2017
DOI: 10.1590/s0102-865020170080000001
|View full text |Cite
|
Sign up to set email alerts
|

Perconditioning combined with postconditioning on kidney ischemia and reperfusion

Abstract: Purpose: To evaluate if combination of perconditioning and postconditioning provides improved renal protection compared to perconditioning alone in a model of renal reperfusion injury. Methods: Thirty rats were assigned into 6 groups: normality; sham; ischemia and reperfusion; postconditioning; perconditioning; perconditioning + postconditioning. Animals were subjected to right nephrectomy and left renal ischemia for 30 minutes. Postconditioning consisted of 3 cycles of 5 min renal perfusion followed by 5 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The procedure of the I/R injury model was performed as previously described [30]. In short, I/R injury was achieved by unilateral clamping (micro aneurysm clamps) in one renal pedicle for 30 min under general inhalation anaesthesia (3% isoflurane and oxygen).…”
Section: Methodsmentioning
confidence: 99%
“…The procedure of the I/R injury model was performed as previously described [30]. In short, I/R injury was achieved by unilateral clamping (micro aneurysm clamps) in one renal pedicle for 30 min under general inhalation anaesthesia (3% isoflurane and oxygen).…”
Section: Methodsmentioning
confidence: 99%
“…The protocol using three alternating cycles of 5 minutes of ischemia and reperfusion was chosen, because it was extensively studied in perconditioning research 1 , 26 - 29 , showing promisors results in hepatic, renal and cardiac IR. Costa et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies have been found yet using remote ischemic conditioning technique associated to mesenteric IR injury, in order to assess whether this technique is really capable of attenuating IR injuries in the intestine, while perconditioning was already effective in cases of myocardial 14 , cerebral 20 and renal 13 ischemia injury.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Hindlimb ischemia was achieved using an elastic rubber band tied around the thigh of the left leg 8 , 13 . The remote ischemic conditioning technique was completed at the same time as the end of the main ischemia 13 - 15 , with subsequent reperfusion of 5 minutes.…”
Section: Methodsmentioning
confidence: 99%